New Nitric Oxide Donor NCX 1443: Therapeutic Effects on Pulmonary Hypertension in the SAD Mouse Model of Sickle Cell Disease. Issue 5 (May 2018) - Abid, Shariq; Kebe, Kanny; Houssaïni, Amal; Tomberli, Françoise; Marcos, Elisabeth; Bizard, Emilie; Breau, Marielle; Parpaleix, Aurelien; Tissot, Claire-Marie; Maitre, Bernard; Lipskaia, Larissa; Derumeaux, Genevieve; et al.
Abstract : Abstract: Nitric oxide (NO) donors may be useful for treating pulmonary hypertension (PH) complicating sickle cell disease (SCD), as endogenous NO is inactivated by hemoglobin released by intravascular hemolysis. Here, we investigated the effects of the new NO donor NCX1443 on PH in transgenic SAD mice, which exhibit mild SCD without severe hemolytic anemia. In SAD and wild-type (WT) mice, the pulmonary pressure response to acute hypoxia was similar and was abolished by 100 mg/kg NCX1443. The level of PH was also similar in SAD and WT mice exposed to chronic hypoxia (9% O2 ) alone or with SU5416 and was similarly reduced by daily NCX1443 gavage. Compared with WT mice, SAD mice exhibited higher levels of HO-1, endothelial NO synthase, and PDE5 but similar levels of lung cyclic guanosine monophosphate. Cultured pulmonary artery smooth muscle cells from SAD mice grew faster than those from WT mice and had higher PDE5 protein levels. Combining NCX1443 and a PDE5 inhibitor suppressed the growth rate difference between SAD and WT cells and induced a larger reduction in hypoxic PH severity in SAD than in WT mice. By amplifying endogenous protective mechanisms, NCX1443 in combination with PDE5 inhibition may prove useful for treating PH complicating SCD.